Cost-minimization analysis of intravenous sulbenicillin versus coamoxiclav for cesarean section - Tri Murti Andayani; Umi Athijah; Ali Ghufron Mukti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
The cost of antibiotic prophylaxis sulbenicillin versus coamoxiclav (in term of medication use and treatment of complications) to treat cesarean section was compared.The medical records of patient receiving intravenous sulbenicillin orcoamoxiclav for the treatment of cesarean section in PKU Muhammadiyah Hospital were retrospectively reviewed. Data were collected for patients treated from January 1, 2000 to December 31, 2000. Patient data collected included patient data based, indication of cesarean section, abdominal incision and oral antibiotics. Cost data collected included drug acquisition cost, cost of drug supplies, nursing time to administer the agents and cost of managing complication.The medical records of 98 patients were identified and reviewed. The average length of stay was 4.85 days for the sulbenicillin group and 4.90days for the coamoxiclav group. The average total including the cost of complication was Rp. 140.509 in sulbenicillin group and Rp. 376.310 in coamoxiclav group.In conclusion, the study demonstrates that intravenous coamoxiclav has a higher cost than that of intravenous sulbenicillin. This result can be used to assist institution, clinicians and pharmacists in determining the most appropriate and efficient use of drugs. These data can be a powerful tool to support various clinical and policy drug use decisions, for example included formulary management and drug use policy or guidelines.Key words: antibiotics, cesarean section, cost.